Polyarticular Septic Arthritis Due to Non-Typeable With Concomitant New-Onset Acute Gouty Arthritis - Brian Sanders MD; Mohammed Abdulfatah MD; Mossab Aljuaid MD; Ibrahim Tawhari MD, MPH (SAGE Publishing, 2019)
Haemophilus influenzae is serologically classified into two main categories based on the presence or absence of the polysaccharide capsule. Strains that possess polysaccharide capsules are identified as typeable Haemophilus influenzae , whereas strains that do not have capsules are identified as non-typeable Haemophilus influenza . Only on very rare occasions, Haemophilus influenzae affects adult joints, and almost 95% of cases have been identified as type b serotypes. Coexistence of gouty and septic arthritis is rare but has been reported. We herein report a case of polyarticular septic arthritis caused by non-typeable Haemophilus influenzae in an adult with concomitant new-onset gouty arthritis. The case was successfully treated with surgical debridement and a 4-week course of ceftriaxone.